2012
DOI: 10.1186/ar3551
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chest wall inflammation by whole-body magnetic resonance imaging in patients with spondyloarthritis: lack of association between clinical and imaging findings in a cross-sectional study

Abstract: IntroductionInflammatory involvement of the anterior chest wall (ACW) affects the quality of life of patients with spondyloarthritis (SpA), although involvement of the ACW is often neglected on clinical and imaging evaluation. Whole-body (WB) MRI is an imaging method used to assess the ACW in addition to the sacroiliac joints and spine without inconvenience for patients. Our goals in this study were to describe the distribution of ACW inflammation by WB MRI in both early and established SpA and associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 25 publications
3
39
1
2
Order By: Relevance
“…summarises and presents the results of longitudinal20 21 50 52–54 61 63 64 66–69 71 73 74 76 as well as cross-sectional51 59 60 70 79 studies evaluating correlation with accepted disease activity parameters (Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR)) or pain.…”
Section: Resultsmentioning
confidence: 99%
“…summarises and presents the results of longitudinal20 21 50 52–54 61 63 64 66–69 71 73 74 76 as well as cross-sectional51 59 60 70 79 studies evaluating correlation with accepted disease activity parameters (Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR)) or pain.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a gold standard for diagnosis, it is unclear whether imaging is a better tool than clinical assessment 27,29,30,31,32,33,34,35 . Outside the clinical trial setting, a combination of clinical suspicion and physical examination plus an objective assessment of inflammation (by ultrasound or MRI) would aid in the proper diagnosis of enthesitis, as well as choice of therapy.…”
Section: Rheumatologymentioning
confidence: 99%
“…Only Weber et al 32 have investigated the association between clinical and WBMRI findings for individual entheses but only for the anterior chest wall, and they found no association. Similarly, Song et al 21 found no significant correlations between an MRI enthesitis score and clinical parameters of disease activity.…”
Section: Discussionmentioning
confidence: 99%